ASUHAN KEPERAWATAN KELUARGA PADA ANAK USIA SEKOLAH DENGAN KECANDUAN GAME DI DUSUN GAYAMAN KECAMATAN MOJOANYAR - Venny Riska Wulan Cahyani; Yudha Laga Hadi Kusuma, M.Kep; Eka Diah Kartiningrum, M.Kes (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Interactive patterns allow engaging directly with a child's life. Supervision of parents plays an important role in children's play activities. The purpose of this study was to implement family nursing care for school-age children with game addiction in Dusun Gayaman, Desa Gayaman, Kecamatan Mojoanyar, Kabupaten Mojokerto. The design used in this study way a case study, the study used 2 families. then made nursing diagnoses intervention, implemention and evaluation. Diagnose of tension risk of the role of caregivers his related to the inability of the family to apply the right parenting style and readiness to improve health related to the family's ignorance of the negative impact of the game. The method of collecting data by interviews, observation, and documentation using the family nursing care format.The results obtained from assessment were complaints of both families, namely not knowing and not being able to apply parenting to the negative impact of the game. Interventions and implementation that were carried out was giving time limits, encouraging parents to be assertive in the pattern of children's education. The evaluation obtained family of client's 1 and client 2 said that they understood the appropriate parenting to prevent the negative impact of the game.